The impact of the local dairy cattle farm toward the river water quality in Gunungpati Subdistrict Central Java - E. Widiastuti; Kustono Kustono; Adiarto Adiarto; Nurliyani Nurliyani (Chemical Engineering Diponegoro University, 2015)
People’s awareness on the living environment nowadays is not yet comes up to the dairy-farmer community. In fact, the dairy-farm subsector contributes load pollution in the form of waste. The waste that is produced by a dairy-farm can be in the form of solid waste and liquid waste. There is still no cultivation effort toward the wastes in a traditional dairy-farmyet, thus most of the wastes are disposed to the closest river, so that in the surrounding dairy farm area is frequently found pollution toward the water quality. The aim of this study is to identify the effect of environment pollution that is caused by local dairy farm in Gunungpati Sub-district, especially toward the river water and residents’ well. The result of this study in Nangkasawit Village before and after the dairy farm was build was still under the quality standard for the third rate water quality. In Plalangan Village, the water quality was also under the quality standard, except for COD concentration. In the Sumurejo Village there was an upturn tendency on the observation value, but the water quality was under the quality standard, except for Fe concentration. Based on the Biodiversity Index before and after the dairy farm was established in Nangkasawit, Plalangan, and Sumurejo were 2.22, 1.49, 2.11, 1.90, 1.78, and 1.88, respectively. It means that Nangkasawit showed no pollution before the dairy farm was established, while there was a medium pollution after the dairy farm establishment. In Plalangan, the water was clear, but it was light polluted after the dairy farm was established. In Sumurejo, before and after the dairy farm establishment the water was light category pollution.